Inovasi Penerapan Genially Hybrid Media dalam Pembelajaran Sistem Reproduksi Manusia di SMA pada Era Kurikulum Nasional 2024 - Fadiatur Rosidah; Muhammad Suwignyo Prayogo; Risa Fitria Agustina; Faiqotun Ni’mah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to develop an interactive learning media based on Genially Hybrid for the topic of the Human Reproductive System in senior high schools, aligned with the 2024 National Curriculum. The research employed a Research and Development (R&D) approach using the ADDIE model, focusing on the development stage. The final product consists of three main media: (1) interactive presentation, (2) digital board game, and (3) “Family 100” game show. Each medium was designed according to Mayer’s Multimedia Principles and Cognitive Learning Theory to enhance students’ engagement and conceptual understanding. The results show that Genially Hybrid media successfully integrates visual, verbal, and interactive components that support both face-to-face and online learning flexibly. These media not only enrich learning experiences but also improve students’ motivation and collaboration in mastering abstract biological concepts. This innovation is expected to serve as an initial model for developing effective and adaptive digital learning media that meet the demands of the Society 5.0 era and the 2024 National Curriculum.